2017
DOI: 10.1016/j.cossms.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Analytical transmission electron microscopy at organic interfaces

Abstract: Organic materials are ubiquitous in all aspects of our daily lives. Increasingly there is a need to understand interactions between different organic phases, or between organic and inorganic materials (hybrid interfaces), in order to gain fundamental knowledge about the origin of their structural and functional properties. In order to understand the complex structure-propertyprocessing relationships in (and between) these materials, we need tools that combine high chemical sensitivity with high spatial resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…Sum frequency generation (SFG) spectroscopy and soft X-ray absorption have shown that functional groups of adsorbed chains are oriented at the outermost surface of the adherends. Real-space observation, such as electron microscopy, has revealed the possibility of an interlocking or anchoring effect, , as described by the mechanical theory. Depth profiling techniques such as dynamic secondary ion mass spectroscopy (DSIMS), , X-ray/neutron reflectivity measurements, and confocal Raman scattering have enabled us to examine the interfacial layer formed by the interdiffusion of polymers, of which the thickness directly affects the adhesion strength. However, there seems to be very limited exploration of experimental approaches to electronic theory.…”
Section: Introductionmentioning
confidence: 99%
“…Sum frequency generation (SFG) spectroscopy and soft X-ray absorption have shown that functional groups of adsorbed chains are oriented at the outermost surface of the adherends. Real-space observation, such as electron microscopy, has revealed the possibility of an interlocking or anchoring effect, , as described by the mechanical theory. Depth profiling techniques such as dynamic secondary ion mass spectroscopy (DSIMS), , X-ray/neutron reflectivity measurements, and confocal Raman scattering have enabled us to examine the interfacial layer formed by the interdiffusion of polymers, of which the thickness directly affects the adhesion strength. However, there seems to be very limited exploration of experimental approaches to electronic theory.…”
Section: Introductionmentioning
confidence: 99%
“…Complex materials often include a component of soft matter that is sensitive to structural or chemical alteration when imaged by electron microscopy. These electron beam sensitive components might be organic crystals, polymers, interfaces and hybrid organic-inorganic materials, even some inorganic materials such as hydrates and hydroxides, as well as multiphase solid/liquid and solid/gas systems (1,2). Arguably materials that contain such components constitute the majority of systems of current interest across a wide range of scientific and engineering disciplines including chemistry and chemical engineering, engineering materials, food science, biology and increasingly physics and electronic engineering.…”
Section: Introductionmentioning
confidence: 99%
“…This article and the accompanying one by Goode et al identifies some recent work showcasing progress within the field of interfacial characterization using spectroscopy. [28][29][30]…”
Section: Introductionmentioning
confidence: 99%